Downregulation of Lysosomal Acid Ceramidase Mediates HMGB1-Induced Migration and Proliferation of Mouse Coronary Arterial Myocytes - Yuan, Xinxu; Bhat, Owais M.; Lohner, Hannah; Zhang, Yang; Li, Pin-Lan (Frontiers in Cell and Developmental Biology, 2020)
High-mobility group box 1 protein (HMGB1) has been reported to trigger lysosome destabilization causing a wide of inflammatory diseases. The present study tested whether a lysosomal enzyme, acid ceramidase (AC), plays a critical role in HMGB1-induced alteration in ceramide metabolism and whether such HMGB1-AC interaction is associated with abnormal migration and proliferation of vascular smooth muscle cells (SMCs). We first observed that the expression of AC in the medial layer of mouse coronary arterial wall and colocalization of AC with a lysosome marker Lamp-1. In primary cultured coronary arterial myocytes (CAMs), AC expression and colocalization with Lamp-1 were significantly up-regulated by AC inducer, genistein, but down-regulated by AC inhibitor, N-oleoylethanolamine (NOE). HMGB1 dose-dependently decreased the colocalization of AC with Lamp-1 and reduced mRNA and protein expressions of AC in CAMs, but reversed by genistein. Consistently, HMGB1 significantly induced increases in the levels of long-chain ceramides in CAMs, which were not further enhanced by NOE but blocked by genistein. More importantly, HMGB1 promoted migration and proliferation of CAMs, which were not further increased by NOE but reduced by genistein. Lastly, CAMs isolated from smooth muscle-specific AC knockout mice (AC gene Asah1) exhibited increased ceramide levels and enhanced the migration and proliferation, which resembles the effects of HMGB1 on wild-type CAMs. Together, these results suggest that HMGB1 promotes SMC migration and proliferation via inhibition of AC expression and ceramide accumulation.